2015
DOI: 10.4103/1673-5374.172317
|View full text |Cite
|
Sign up to set email alerts
|

Neuroprotective effects of salidroside on focal cerebral ischemia/reperfusion injury involves the nuclear erythroid 2-related factor 2 pathway

Abstract: Salidroside, the main active ingredient extracted from Rhodiola crenulata, has been shown to be neuroprotective in ischemic cerebral injury, but the underlying mechanism for this neuroprotection is poorly understood. In the current study, the neuroprotective effect of salidroside on cerebral ischemia-induced oxidative stress and the role of the nuclear factor erythroid 2-related factor 2 (Nrf2) pathway was investigated in a rat model of middle cerebral artery occlusion. Salidroside (30 mg/kg) reduced infarct s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
34
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 41 publications
(34 citation statements)
references
References 28 publications
0
34
0
Order By: Relevance
“…Salidroside, a natural compound extracted Rhodiola rosea L, which has long been used as a traditional Tibetan medicine to relieve altitude sickness, other effects on neuro-protection, cardio-protection, anti-depression, anti-fatigue, and anti-tumor have been reported [ 14 , 15 ]. Salidroside is thought to be one of the most effective compounds from Rhodiola rosea L for its multiple functions, such as anti-aging, anti-cancer, anti-inflammation, anti-oxidative stress, hepatoprotective properties and neuroprotective effect [ 31 – 36 ]. But the specific molecular target of salidroside has not been reported.…”
Section: Discussionmentioning
confidence: 99%
“…Salidroside, a natural compound extracted Rhodiola rosea L, which has long been used as a traditional Tibetan medicine to relieve altitude sickness, other effects on neuro-protection, cardio-protection, anti-depression, anti-fatigue, and anti-tumor have been reported [ 14 , 15 ]. Salidroside is thought to be one of the most effective compounds from Rhodiola rosea L for its multiple functions, such as anti-aging, anti-cancer, anti-inflammation, anti-oxidative stress, hepatoprotective properties and neuroprotective effect [ 31 – 36 ]. But the specific molecular target of salidroside has not been reported.…”
Section: Discussionmentioning
confidence: 99%
“…For example, studies have reported that salidroside increases the neurological severity scores and reduces the cerebral edema and infarction volume at doses of 12 or 24 mg/kg (Zou YQ et al, 2009;Shi et al, 2012;Han, 2013). Our previous studies demonstrated that salidroside displayed strong and specific neuroprotective properties in MCAO-induced stroke with treatment (50 mg/kg, administered 1 h after the operation) once daily for 1, 2, and 6 days, or with only a two-time administration at a dose of 30 mg/kg (administered immediately before cerebral ischemia and after reperfusion) (Han et al, 2015;Lai et al, 2015;Lai et al, 2018). In a previous study, we found salidroside (30 mg/kg) reduced infarct size in 2,3,5-triphenyltetrazolium chloride-stained brain slices and improved histological changes in the cortex and striatum as revealed by Nissl staining (Han et al, 2015).…”
Section: Discussionmentioning
confidence: 99%
“…Our previous studies demonstrated that salidroside displayed strong and specific neuroprotective properties in MCAO-induced stroke with treatment (50 mg/kg, administered 1 h after the operation) once daily for 1, 2, and 6 days, or with only a two-time administration at a dose of 30 mg/kg (administered immediately before cerebral ischemia and after reperfusion) (Han et al, 2015;Lai et al, 2015;Lai et al, 2018). In a previous study, we found salidroside (30 mg/kg) reduced infarct size in 2,3,5-triphenyltetrazolium chloride-stained brain slices and improved histological changes in the cortex and striatum as revealed by Nissl staining (Han et al, 2015). To further validate the effect of salidroside on cerebral ischemia/reperfusion, we used the balance beam test and foot fault test.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It has been demonstrated that SAL is neuroprotective against ischemic cerebral injury, a leading cause of disability and mortality worldwide and is therefore considered to be a major public health problem ( 5 ). It has been demonstrated that SAL reduces the infarct volume and improves neurological deficit scores in a rat model of transient focal cerebral ischemia and reperfusion ( 6 ). In addition, SAL improves learning and spatial memory during hypoxia treatment, indicating that SAL has a neuroprotective effect during hypoxia ( 7 ).…”
Section: Introductionmentioning
confidence: 99%